2016
DOI: 10.4314/tjpr.v15i11.4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and <i>in-vitro</i> cytotoxicity of zinc oxide nanoparticles against osteoarthritic chondrocytes

Abstract: Purpose: To prepare zinc oxide nanoparticles (ZnO NPs) by various techniques, including x-ray diffraction (XRD), Fourier transform-infrared spectroscopy (FT-IR), ultraviolet-visible spectroscopy (UV-Vis), energy-dispersive x-ray spectroscopy (EDS) and transmission electron microscopy (TEM). The cytotoxicity of the NPs against human osteoarthritic chondrocytes was studied using eosin Y test method. Results: The change in color of the reaction solution from colorless to pale white within 1 h indicated the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…This study is aimed at finding out the optimum parameters for the extraction of components from Piper betle leaf using deionized water (18.2 mΩ•cm resistivity) [28,42,[46][47][48]. The optimum conditions were selected based on the extract yield by varying parameters: (1) ratio between material amount (g) and solvent volume (ml) (1 : 5, 1 : 10, and 1 : 15, w/v), (2) extraction temperature (70, 80, and 90°C), and (3) extraction time (15, 30, and 60 minutes).…”
Section: Preparation Of Piper Betle Leaf Extract (Et)mentioning
confidence: 99%
See 3 more Smart Citations
“…This study is aimed at finding out the optimum parameters for the extraction of components from Piper betle leaf using deionized water (18.2 mΩ•cm resistivity) [28,42,[46][47][48]. The optimum conditions were selected based on the extract yield by varying parameters: (1) ratio between material amount (g) and solvent volume (ml) (1 : 5, 1 : 10, and 1 : 15, w/v), (2) extraction temperature (70, 80, and 90°C), and (3) extraction time (15, 30, and 60 minutes).…”
Section: Preparation Of Piper Betle Leaf Extract (Et)mentioning
confidence: 99%
“…Recently, many reviews on green technology-based synthesis of nanoparticles have shown that they are promising methods for large-scale production of metal nanoparticles for biomedical applications. A wide variety of plant extracts are used for the biosynthesis of ZnO NPs, and the results proved that ZnO NPs are safe for human use alternative to Ag NPs or other metal nanoparticles [28][29][30][31][32][33][34]. Piper betle L. known as a traditional herbal medicinal plant is associated with the control of caries and periodontal disease, inflammation, antimicrobial activity, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this issue, the demand for the production of nanoparticles with safer methods, such as biological methods (also known as green method), is increasing (Agarwal, Kumar, & Rajeshkumar, 2017;Song & Kim, 2009). In these methods, plants or microorganisms or substances already exist in nature are commonly applied for nanoparticles synthesis (Agarwal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%